Factors influencing individual investor's decision / Arifha Mohamad...[et al.] - Mohamad, Arifha; Tahir, Nor Suziwana; Ahmad, Yarina (Universiti Teknologi MARA, Kedah, 2017)
Investors had to make wise investment decision to achieve a positive social, cultural, and environmental benefit and some measure of financial return. Most of the investors, not only in Malaysia have the problem of irrational investment decision compared to the institutional investors. While there are many factors influencing investment decision, this paper only concentrates on four main factors of shareholders' investment in the international context as well as demonstrated to be as key determinants in the Malaysian context: accounting information, personal financial needs, gender, and advocate recommendation. This paper reviews relevant literatures and reports related to shareholders' investment decision making and its contributing factors. This paper argues that these four determinants of shareholders' investment are important to avoid losses and bankruptcy.